The Effect of Thailand and India Free Trade Agreement (TIFTA) Towards Thailand - เทียบแก้ว, วิชนี; คล้ายทับทิม, จุฑาทิพ (Thai Interdisciplinary and Sustainability Review, 2019)
This thesis aimed to study the effect of Thailand-India Free Trade Agreement in 2004-2011 and the factors that affect Thailand-India Free Trade Agreement. The results of the thesis "The Effect of Thailand-India Free Trade Agreement (TIFTA) towards Thailand" were as follows; Thailand-India Free Trade Agreement causes the rapid expansion of trade in goods. The expansion of trade in services especially tourism sector. Moreover Thailand-India Free Trade Agreement also increases Thailand-India investment. However, Thailand-India Free Trade Agreement has caused a negative impact on the production of Thailand due to the relocation of Thailand’s company to India and trade barriers from India. The factors that affect Thailand-India Free Trade Agreement are as follows; economic integration under multilateral framework such as WTO has not been accomplished, many countries have turned to bilateral agreement instead. Secondly, India has played a vital role economic role in the Post-Cold War as well as the high potential of India market. Moreover, India will be the gateway of economic cooperation between Thailand and the countries in South Asia.